Pharmaceutical expenditure changes under the volume-based procurement policy: Effects and influencing factors - Ying Yang; Yuanhui Duan; Lei Zhou; Sisheng Gan; Zongfu Mao; Furong Wang (PLoS ONE, 2025)
Objectives To estimate the impact of China’s volume-based procurement (VBP) policy on the expenditure of both policy-covered and uncovered drugs, and to identify the elements that contribute to drug expenditure changes under VBP policy. Methods Using national drug procurement data of public medical institutions, this study included 25 policy-covered VBP drugs and 99 policy-uncovered alternative drugs as samples, seven “4+7” pilot cities and eight “4+7” expansion provinces as observation regions. Time-varying difference-in-difference (DID) model was applied to quantify policy impact on drug expenditures. The drug expenditure index decomposition method was employed to analyze the determinants of drug expenditure changes following VBP policy. Results The expenditure of VBP drugs significantly decreased by 42.19% after VBP policy (β = −0.55, p < 0.001), while alternative drugs increased by 11.52% (β = −0.11, p < 0.001), with a significant reduction in the overall expenditure of observed drugs (β = −0.05, p < 0.001). The decrease of VBP drug expenditures showed a trend of tertiary hospital (β = −0.64, p < 0.001) > secondary hospital (β = −0.57, p < 0.001) > primary healthcare centers (β = −0.39, p < 0.001). The index decomposition showed that manufacturer structure index (IM) decline was the primary driver for expenditure reduction of policy-covered drugs, with the IM decrease of 54.17% in pilot cities and 40.86% in expansion regions. The secondary driver was the price index (IP), with a decline of 31.68% in pilot cities and 36.08% in expansion regions. The restraining factor was the quantity index (IQ), increasing by 92.54% in pilot cities and 52.04% in expansion regions. IQ also drove the increase in alternative drug expenditures, increasing by 95.56% in pilot cities and 32.76% in expansion regions. Conclusion VBP policy effectively promoted the decline of total drug expenditures, primarily through manufacturer-level market displacement and the absolute price reduction. However, the “spillover effect” of alternative drugs weakened the overall effect on cost control. Strengthening holistic governance and improving the quality and intensiveness of drug use are important directions for future policy perfection.